1981
DOI: 10.1002/bdd.2510020106
|View full text |Cite
|
Sign up to set email alerts
|

A propranolol radioimmunoassay and its use in the study of its pharmaco‐kinetics following low doses

Abstract: A radioimmunoassay has been developed for propranolol with a sensitivity of 2.37 nmol l-1 in unextracted plasma using a 50 microliter sample. Plasma concentration measurements were made on samples from volunteers for up to 8 h after they had been given 5, 10, or 40 mg of propranolol by mouth. Analysis of the results showed that mean elimination half-lives and total body clearances were similar following each of the doses and that the area under the curve was proportional to the dose. Steady-state propranolol c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 10 publications
2
9
0
Order By: Relevance
“…This argument can be further verified by comparison of the mean observed clearance (CL) 0.82 L/h/kg (95% CI: 0.64-1.00) [26][27][28]46,47 with mean predicted clearance 0.99 L/h/kg (95% CI: 0.70-1.2) after IV administration. Similarly, CL/F in healthy individuals was also comparable, as its observed and reported values were 217 L/h (95% CI: 183.6-250.80) 26,[29][30][31][32][33]46,[48][49][50][51][52] and 183.3 L/h (95% CI: 169.9-196.6), respectively. Furthermore, the AFE value for CL (0.83 and 1.15 after IV and oral dose predictions) strengthened the argument that the developed PBPK model was predicting the disposition of the drug precisely (Table 4).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This argument can be further verified by comparison of the mean observed clearance (CL) 0.82 L/h/kg (95% CI: 0.64-1.00) [26][27][28]46,47 with mean predicted clearance 0.99 L/h/kg (95% CI: 0.70-1.2) after IV administration. Similarly, CL/F in healthy individuals was also comparable, as its observed and reported values were 217 L/h (95% CI: 183.6-250.80) 26,[29][30][31][32][33]46,[48][49][50][51][52] and 183.3 L/h (95% CI: 169.9-196.6), respectively. Furthermore, the AFE value for CL (0.83 and 1.15 after IV and oral dose predictions) strengthened the argument that the developed PBPK model was predicting the disposition of the drug precisely (Table 4).…”
Section: Discussionsupporting
confidence: 73%
“…Data from 22 clinical studies (7 for IV administration and 15 for oral administration) in healthy individuals was extracted. One-third (3 IV 26-28 and 5 oral [29][30][31][32][33] ) of which were used for the development of the PBPK model and the rest of the two-thirds (4 IV and 10 oral) were used for subsequent model verifications. All the observed data sets were used for model evaluation.…”
Section: Materials and Methodology Clinical Pharmacokinetic Datamentioning
confidence: 99%
“…Although it has been shown that the liver metabolism is non-linear, saturating at high blood levels, this non-linearity only becomes significant at doses above 200 mg/day [35]. At lower doses, both the liver metabolism and PO absorption appear to be linear [36,37]. All the data that will be used here fall in this linear dose range.…”
Section: Resultsmentioning
confidence: 99%
“…The plasma samples were assayed in duplicate using the specific radioimmunoassay for propranolol previously developed (9). Although the sensitivity of the assay is 2 .…”
Section: Assay Of Plasma Samplesmentioning
confidence: 99%
“…A recently developed radioimmunoassay technique (9) has enabled propranolol to be measured following low doses of drug, allowing subjects to take significantly less proprano-lo1 than in previous studies (8,10). Accordmgly the plasma concentration profiles following 10 mg propranolol hydrochloride from two different tablets and a freshly prepared solution were compared.…”
Section: Introductionmentioning
confidence: 99%